The government website as user's information source: A model of user satisfaction, information, and system quality - Ernungtyas, Niken Febrina; Boer, Rino Febrianno; Qadrifa, Sabrina Sofi (Universitas Negeri Yogyakarta, 2023)
The Ministry of Religious Affairs of the Republic of Indonesia uses a website to disseminate news and publications to the public. An effective strategy for developing a successful website is to build a positive user experience that leads to a positive attitude from users towards the website. User experience in terms of optimizing website utilization has not been well explored, especially regarding satisfaction. Satisfaction is influenced by information quality and system quality factors. Information quality encompasses 5 variables (completeness, accuracy, format, currency, availability) and system quality consists of nine variables (reliability, flexibility, accessibility, responsiveness, integration, usability, functionality, design appeal, efficiency). This study assessed the effect of information quality and system quality on the satisfaction of using the Ministry of Religious Affairs' website. The target population of this study were all users who had accessed the website at least once in the last three months. The data were collected from 420 respondents and analyzed using PLS-SEM. The findings indicated that the hypothesis of the variables completeness, accuracy, format, currency, availability, reliability, flexibility, accessibility, responsiveness, integration, usability, and functionality is not supported. However, the results of this research confirmed the positive and significant effect of design appeal and efficiency on satisfaction.